2010
DOI: 10.1038/jcbfm.2010.80
|View full text |Cite
|
Sign up to set email alerts
|

A Retinoic Acid Receptor Agonist Am80 Rescues Neurons, Attenuates Inflammatory Reactions, and Improves Behavioral Recovery after Intracerebral Hemorrhage in Mice

Abstract: Am80 (tamibarotene) is a retinoic acid receptor (RAR) agonist clinically available for treatment of acute promyelocytic leukemia. As intracerebral hemorrhage (ICH) accompanies inflammatory reactions in the brain and also because retinoids may suppress activation of microglia, we investigated the effect of Am80 on collagenase-induced experimental model of ICH in adult mice. Daily oral administration of Am80 (5 mg/kg) starting from 1 day before or from up to 6 hours after intrastriatal injection of collagenase s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 38 publications
1
49
0
Order By: Relevance
“…1 Although several therapeutic strategies for management of ICH are currently in clinical practice, 1 virtually none are aimed at neuroprotection. Basic research has demonstrated that various drugs that possess antioxidative, anti-inflammatory, or neurotrophic/neuroprotective properties produce therapeutic effects on ICH animal models 2,3 ; however, effective drug therapies for ICH are yet unavailable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Although several therapeutic strategies for management of ICH are currently in clinical practice, 1 virtually none are aimed at neuroprotection. Basic research has demonstrated that various drugs that possess antioxidative, anti-inflammatory, or neurotrophic/neuroprotective properties produce therapeutic effects on ICH animal models 2,3 ; however, effective drug therapies for ICH are yet unavailable.…”
mentioning
confidence: 99%
“…3,4 Astrocytes accumulate in the perihematomal region 5 and induce toxic edema, provoke inflammation, release cytotoxins, and form scars after ICH. 6 Moreover, neutrophils, macrophages, and microglia are major central nervous system sources of cytokines, chemokines, and other immunomolecules 4 and are thought to provoke secondary brain damage after ICH.…”
mentioning
confidence: 99%
“…44,45) In an intracerebral hemorrhage model in mice, Am80 significantly attenuated neuronal damage in the striatum, and this effect was associated with suppression of activation of microglia/macrophages in the perihematoma region. 46) A similar suppression of inflammatory cell death caused by oxidative stress, nitroxide or other stresses seems likely to occur in other brain areas. Jarvis et al 35) reported that Am580 significantly suppressed cell death of cultured cortical neurons exposed to 10 µM Aβ.…”
Section: Suppression Of Inflammationmentioning
confidence: 95%
“…23) In the case of ICH in the striatum, RAR stimulation by Am80 partially protected striatal neurons within the hematoma from degeneration, diminished activation of microglia/macrophages in the perihematomal region, and alleviated neurological dysfunction. 20) Notably, a subsequent study revealed that Am80 inhibited accumulation of APP in the perihematomal region, suggesting that the drug had a protective effect on axonal function. 24) These results prompted us to examine the effect of Am80 on ICH accompanied by the injury of the internal capsule.…”
Section: Exploration Of Drugs For Ich With Axonal Tract Injurymentioning
confidence: 99%
“…19) We have made several attempts to find out novel therapeutic targets for ICH, using a conventional mouse model of ICH induced by collagenase injection into the striatum. [20][21][22] In the course of these investigations, we found that a retinoic acid receptor (RAR) agonist Am80 produced a beneficial effect. RAR is expressed in neurons, astrocytes and microglia and therefore widely distributed in the central nervous system.…”
Section: Exploration Of Drugs For Ich With Axonal Tract Injurymentioning
confidence: 99%